Polskie ekwiwalenty semantyczne rosyjskiego rzeczownika ярость - Behrendt-Bartkowska, Sonia (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The purpose of this article is to compare the Russian noun ярость (rage) and its Polish semantic equivalents (gniew, wściekłość, pasja, furia) reported by Russian-Polish and Polish-Russian Dictionaries. Monographs, articles and dictionary entries have been used to analyse the terms and to create new definitions of feelings based on the Natural semantic metalanguage (NSM). The new definitions were written using sixty semantic primes, are universal for all languages, which helped to show similarities or differences between such difficult terms as feelings. Using this method, symmetry and asymmetry of equivalence have been found between Russian and Polish words.